La comunicación no verbal en el montaje escénico del Grupo Malayerba. - Gordón Vinueza, Andrea Valeria (2013)
Communication is present in the first demonstrations that humans have done to communicate with others. The theater has its roots in these events spectacular expression were performed in order to represent spaces of everyday life and their gods. The theater is a communication system which demonstrate linguistic and non-linguistic signs, which are linked to form all the theatrical. This research focuses on the analysis of nonverbal communication in the staging of the play "The School takes" Theatre Laboratory group Malayerba.